Transport coefficients of a relativistic plasma - Pike,OJ; Rose,SJ (Physical Review E, 2016)
In this work, a self-consistent transport theory for a relativistic plasma is developed.Using the notation of Braginskii [S. I. Braginskii, in Reviews of Plasma Physics, ed. M. A.Leontovich (1965), Vol. 1, p.174], we provide semi-analytical forms of the electrical resistivity,thermoelectric and thermal conductivity tensors for a Lorentzian plasma in a magnetic field.This treatment is then generalized to plasmas with arbitrary atomic number by numericallysolving the linearized Boltzmann equation. The corresponding transport coefficients arefitted by rational functions in order to make them suitable for use in radiation-hydrodynamicsimulations and transport calculations. Within the confines of linear transport theory andon the assumption that the plasma is optically thin, our results are valid for temperatures upto a few MeV. By contrast, classical transport theory begins to incur significant errors abovekBT ∼ 10 keV, e.g., the parallel thermal conductivity is suppressed by 15% at kBT = 20keV due to relativistic effects